Histopathological characterisation of colitis in Western lowland gorillas (Gorilla gorilla ssp. gorilla) - Morey Matamalas, Antonia (2022)
In captive gorillas, ulcerative colitis is an important cause of morbidity and mortality with no established definite aetiopathogenesis. The aim of the study was to histopathologically characterise colon lesions in captive western lowland gorillas (Gorilla gorilla ssp. gorilla) and to investigate the feasibility of applying the Nancy index, a disease activity scoring system for ulcerative colitis in humans. Colon samples from 21 animals were evaluated based on histopathological characteristics for the diagnosis of inflammatory bowel disease (IBD) in humans and divided into acute and chronic changes. The Nancy index, graded 0 to 4, was applied to all cases. Special stains including Ziehl-Neelsen, Warthin-Starry, Gram and Periodic Acid Schiff reaction were used to identify potential aetiological agents. Most common acute changes included neutrophils in the lamina propria (17/18, 94%), mucosal and submucosal oedema (12/18, 67%), and crypt abscesses (8/18, 44%). Most common chronic changes were lamina proprial lymphoplasmacytic infiltrates (17/18, 94%) and crypt dilation/distortion (6/18, 33%). Based on the Nancy index, 4/21 (19%) cases were graded as grade 4 (the highest grade), 2/21 (10%) were identified as grade 3, 11/21 (52%) grade 2, and 4/21 (19%) cases were graded 0. The changes in the colon observed in our study show comparable characteristics to the acute phase of ulcerative colitis described in humans. No unifying aetiopathogenesis could be identified. The Nancy index proved a valuable tool for the standardisation of disease activity grading and comparison for further studies in gorilla colitis.